Child Abuse Suffered by Saul in Richard Wagamese’s Indian Horse - ulya, husnia naylil (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study investigates the child abuse suffered by the protagonist, Saul, in Richard Wagamese's novel "Indian Horse." The study explores the different forms of abuse Saul faced and examines how these experiences influenced his life, as portrayed in the novel. This study adopts literary criticism and employs a psychological approach and McCabe and Murphy's theory of child abuse. The data used in this study consists of words, phrases, and sentences extracted from Richard Wagamese's novel "Indian Horse," published by Douglas & McIntyre in 2012. The findings reveal that while residing in St. Jerome, Saul suffered abuse from both his teacher and caregiver. The forms of abuse encompass physical, emotional, sexual, and neglectful mistreatment. Physical abuse involved the act of rough objects being scratched against Saul's body. Emotional abuse included instances of rejection, terrorization, and isolation. Additionally, Saul endured sexual abuse from his teacher. Neglect also played a part, encompassing physical, educational, and emotional neglect. The significant impact of these childhood traumas on Saul's adult life is evident in the results. Saul's coping mechanisms led to alcoholism and aggressive behavior. He withdrew from his surroundings, experiencing profound trauma, depression, and low self-esteem due to the abuse he suffered during his formative years.